2015
DOI: 10.1007/s10802-015-0028-5
|View full text |Cite
|
Sign up to set email alerts
|

Early Childhood Reticent and Solitary-Passive Behaviors and Adjustment Outcomes in Chinese Children

Abstract: Little is known about the developmental outcomes of children's social withdrawal in non-Western societies. The present study examined how two main forms of social withdrawal, social reticence and solitary-passive behavior, in early childhood were associated with adjustment in late childhood in Chinese children (75 boys and 92 girls). Data on reticent and solitary-passive behaviors were collected at 4 years of age from laboratory observations. Follow-up data on school, behavioral, and psychological adjustment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…Our results contribute to a growing body of research carried out in distinct cultural contexts (e.g., Gullone et al, 2006; Rubin et al, 2006; Sette et al, 2014; Chen et al, 2015; Ojanen et al, 2017), by showing that Portuguese anxiously withdrawn adolescents experience greater difficulties and less success in their contact with the peer group. Consistent with prior research (e.g., Rubin et al, 2006), we found that anxious withdrawal significantly predicted higher levels of peer exclusion and victimization, as well as lower popularity/sociability.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Our results contribute to a growing body of research carried out in distinct cultural contexts (e.g., Gullone et al, 2006; Rubin et al, 2006; Sette et al, 2014; Chen et al, 2015; Ojanen et al, 2017), by showing that Portuguese anxiously withdrawn adolescents experience greater difficulties and less success in their contact with the peer group. Consistent with prior research (e.g., Rubin et al, 2006), we found that anxious withdrawal significantly predicted higher levels of peer exclusion and victimization, as well as lower popularity/sociability.…”
Section: Discussionsupporting
confidence: 64%
“…At present, researchers have yet to examine the significance of friendship for anxiously withdrawn Portuguese youth. Most studies of anxious withdrawn behavior have involved samples in North America (e.g., Rubin, 1993; Gazelle and Rudolph, 2004; Rubin et al, 2006), Asia (e.g., China – Chen et al, 2014, 2015), Australia (e.g., Gullone et al, 2006), Cuba (Valdivia et al, 2005), South America (e.g., Saldarriaga et al, 2012), and some countries in Europe (e.g., Italy, Finland and Netherlands – Cillessen et al, 1992; Casiglia et al, 1998; Sette et al, 2014; Ojanen et al, 2017). Few, if any, studies have been published on samples based in Portugal and, therefore, virtually nothing is known about the causes, correlates and consequences of withdrawn behavior among Portuguese youth.…”
Section: Introductionmentioning
confidence: 99%
“…The process involved in the relations may be complex and need to be investigated systematically. In particular, considering that recent findings have suggested that different kinds of temperamental withdrawal behaviors may play different roles in maladaptive development in the Chinese context (Chen et al., ), it would be important to measure children's temperamental withdrawal tendency after they begin to socialize with peers in the future. An additional limitation is the use of only maternal reports of infant temperamental withdrawal and toddlers’ behavior problems, rather than both parents’ reports.…”
Section: Discussionmentioning
confidence: 99%
“…The current study examined the relations between infants’ temperamental withdrawal and behavior problems assessed in toddlerhood. According to Chen et al.’s () findings in the Chinese cultural context and Edwards and Hans’ () findings on infants, we hypothesized that infants who were rated as highly withdrawn by their mothers at 6 months of age would exhibit increased internalizing and externalizing problems at 1 and 2 years of age. In addition to these direct effects, we also explored MSID observed in infant–mother interaction at 6 months of age as a moderator of the associations between infant temperamental withdrawal and subsequent behavior problems.…”
Section: Current Studymentioning
confidence: 97%
See 1 more Smart Citation